Locus of Control and Academic Resilience: Dynamics in Students Working on Thesis - Ageta Nestri Gondhowati; Rr. Siti Suminarti Fasikhah; Ahmad Sulaiman (PSIKODIMENSIA Kajian Ilmiah Psikologi, 2025)
Locus of control refers to an individual’s belief about the extent to which internal and external factors influence students’ processes in completing their thesis. Academic resilience, meanwhile, is the ability of students to endure, recover, and rise when faced with challenges and difficulties during thesis writing. The phenomenon in which students struggle to regulate their emotions and manage stress when encountering obstacles can affect their level of academic resilience. The aim of this study is to examine the dynamics between locus of control and academic resilience in students who are currently working on their thesis. The researcher used a simple random sampling technique to select research subjects and obtained 300 students as subjects of this study. This study used a quantitative method with a correlational approach and simple linear regression analysis. Based on the results of the correlation test, a significant positive relationship was found between locus of control and academic resilience in students working on their thesis (r = 0.450; p = 0.001). Simple linear regression analysis also showed that locus of control predicts academic resilience in students (r² = 0.202; t = 8.693; p = 0.001).